The Stigma Experienced by Terminally Ill Patients: Evidence From a Portuguese Ethnographic Study. Issue 4 (1st October 2016) - Hilário, Ana Patrícia
ABSTRACT: The aim of this study was to offer an understanding of the ways in which terminally ill patients may face discrimination due to their visibly altered body. An ethnographic approach was adopted and fieldwork was conducted over 10 months in 2 inpatient hospice units in Portugal. Participant observation was complemented by 50 in-depth interviews with terminally ill patients, family members, and hospice staff. The stigma experienced by terminally ill patients derived mostly from the behavior of peers, extended family members, and friends toward their visibly altered body. There was no evidence that these patients were discredited by their immediate family when they became visibly unwell; unlike what has been reported in previous studies. This finding could be related to the strong familial culture of Portuguese society.